Classification of Textures Using Filter Based Local Feature Extraction - YILDIZ, KAZIM; BÖCEKÇİ, VEYSEL GÖKHAN (E D P SCIENCES, 2016)
In this work local features are used in feature extraction process in image processing for textures. The local binary pattern feature extraction method from textures are introduced. Filtering is also used during the feature extraction process for getting discriminative features. To show the effectiveness of the algorithm before the extraction process, three different noise are added to both train and test images. Wiener filter and median filter are used to remove the noise from images. We evaluate the performance of the method with Naive Bayesian classifier. We conduct the comparative analysis on benchmark dataset with different filtering and size. Our experiments demonstrate that feature extraction process combine with filtering give promising results on noisy images.
Keywords: BINARY PATTERNS